Information system for reporting project performance according to the annual action plan of Faculty of Education, Sisaket Rajabhat University - Tonggund, Runsamee (Research and Development Journal Sisaket Rajabhat University, 2020)
The purpose of this research is to develop an information system for reporting project performance according to the annual action plan. Case study Faculty of Education, Sisaket Rajabhat University. The researcher has developed a system to facilitate personnel in all departments. As well as executives can check information through the internet network and obtain project information according to the annual action plan for efficiency and effectiveness. Reducing redundant work times and being quick and easy to use Data storage Search and presenting useful information to practitioners.This research is a developmental research by using the principles of information system development cycle. Starting from studying the problem and then bringing the problem to analyze. Then design the database using MySQL database system and develop the system with PHP language. Once the system has been completed, it is tested and installed and evaluated the satisfaction from the administrators, professors and staff.Research results show that information system can report the results of the project implementation according to the annual action plan. And report the operating results quickly and accurately from the evaluation of user satisfaction with the information system. Found that in the overall picture, users are satisfied with the highest level. Keywords: Information system for reporting project performance